32: EVEN‐AGE MANAGEMENT TURKEYS AND TURKEY HUNTERS A NEW STUDY* - Jack Ward Thomas; James C. Pack; John D. Gill; R. Wayne Bailey (Wildlife Society Bulletin)
ABSTRACT Methods for coordinating even‐aged hardwood management and turkey‐habitat management are being studied in West Virginia. The study utilizes a 20,000‐acre area (10,000 acres in control); 1,620 acres are treated as clear‐cuts and 840 are of intermediate cut. Effects of the treatment on eastern turkeys (Meleagris gallopavo silvestris), white‐tailed deer (Odocoileus virginianus), squirrels (Sciurus spp.), ruffed grouse (Bonasa umbellus), and on attitudes and behavior of hunters are being determined. Three techniques are used to measure wildlife populations. Some 1,200 to 1,400 hunters are interviewed annually.